Optimization of intersection control scheme considering phase-movement-combination under automated vehicles environment - Xiao, Wenbin; Zhu, Shunying; Wang, Daobin; Liu, Wei (Transport, 2021)
For signal control intersection, the Phase-Movement-Combination (PMC) styles could directly impact the control performance of the signal scheme. Automated vehicles use mechatronics technology to drive autonomously and safely according to the predetermined lane trajectory, which caused the phase movement combination and Phase Combination (PC) schemes become more and more complicated. Therefore, this paper proposed a method to consider the extensive PMC styles by fractionalizing movement compatibility relationships, and used discrete mathematics to calculate overall Feasible Phase Combination (FPC) schemes according to the requirements of the signal phase. A corresponding optimal timing model was also established for FPC schemes by minimizing the average vehicle delay and maximizing the intersection capacity. Results were compared against the conventional PC schemes for a variety of demand scenarios. It was concluded that the proposed signal control optimization method was effective to optimize the intersection control scheme, depending on different demand scenarios.First published online 19 August 2020